Effects of Precipitation Hardening Heat Treatment on Mechanical Properties of Recycled Aluminium, Silicon Alloy - Elisha, Kenneth; Mangai, Mahan Morgan; Timothy, Kevin Yanan (Direct Research Journal of Engineering and Information Technology, 2024)
The objective of this research was to determine the effect of precipitation heat treatment on mechanical properties of recycled Aluminium- Silicon alloy. Aluminium block engine scrap was melted and cast via sand casting method the samples were machined into standard specifications of hardness, tensile and impact with lathe machine. The samples where solution treated at 500°C, 515°Cand 530°C in a heat treatment furnace to obtain solid solution and quenched in water at room temperature. The samples where aged at 200°C, 175°C and 150°C for 3 hours each to obtain precipitation hardening.  The samples where then subjected to tensile strength test, impact test and hardness test before and after heat treatment to study the effect of precipitation hardening heat treatment on the mechanical properties. From the results of the control sample, solution temperatures and ageing temperatures, the control sample has a UTS, impact energy, and Vickers hardness of (135.36 Mpa, 1.04J, and 96.9 HV) respectively, and at 500°C &200°C (180.32Mpa, 1.04J and 130.7HV) respectively, at 515°C &175°C (201.18Mpa, 1.13J and 154.6HV) respectively and at 530°C &150°C (185.19Mpa, 1.08J and 113.2HV) respectively.  It was observed an increase in the tensile strength with UTS of 201.18Mpa, impact energy of 1.13Joule and hardness of 154.6 HV values. This shows that 175°C ageing temperature has the best evaluation of tensile strength, impact strength and hardness at room temperature.
Keywords: Heat treatment; mechanical properties; Aluminium; silicon and alloy